2019
DOI: 10.1016/j.gfj.2018.02.003
|View full text |Cite|
|
Sign up to set email alerts
|

What is a better cross-hedge for energy: Equities or other commodities?

Abstract: Can energy futures returns be effectively hedged? If so, what is the best hedge instrument? We study the hedging performance of several cross-hedges including the equity market, oil and gas equities, precious metals, industrial metals, and agricultural commodities. Our main conclusion is that cross-hedging fluctuations in the energy market is generally not very effective and that any reduction in overall risk is small unless the oil and gas equity index is used. While all cross-hedges have performed better sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…The severity of the recent global financial crisis highlighted the risks associated with portfolios containing only conventional financial market assets (Caballero et al, 2008;Lau et al, 2017;Muteba Mwamba et al, 2017;. This in turn has triggered an interest in considering investment opportunities in the energy (specifically oil) market (Degiannakis and Filis, 2017;Olson et al, 2017Olson et al, , 2018Bahloul et al, 2018;Cunado et al, 2019), since the recent financialization of the commodity (including oil) market (Tang and Xiong, 2012;Silvennoinen and Thorp, 2013;Bonato and Taschini, 2016;Gogolin and Kearney, 2016;Pradhananga, 2016; has resulted in an increased participation of hedge funds, pension funds, and insurance companies in the market, with investment in oil now being considered as a profitable alternative instrument in the portfolio decisions of financial institutions (Akram, 2009;Fattouh et al, 2013;Büyükşahin and Robe, 2014;Antonakakis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the recent global financial crisis highlighted the risks associated with portfolios containing only conventional financial market assets (Caballero et al, 2008;Lau et al, 2017;Muteba Mwamba et al, 2017;. This in turn has triggered an interest in considering investment opportunities in the energy (specifically oil) market (Degiannakis and Filis, 2017;Olson et al, 2017Olson et al, , 2018Bahloul et al, 2018;Cunado et al, 2019), since the recent financialization of the commodity (including oil) market (Tang and Xiong, 2012;Silvennoinen and Thorp, 2013;Bonato and Taschini, 2016;Gogolin and Kearney, 2016;Pradhananga, 2016; has resulted in an increased participation of hedge funds, pension funds, and insurance companies in the market, with investment in oil now being considered as a profitable alternative instrument in the portfolio decisions of financial institutions (Akram, 2009;Fattouh et al, 2013;Büyükşahin and Robe, 2014;Antonakakis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Raza et al (2018) studies the different hedging strategies by considering the real estate and commodity index of the US and supported that the commodity index can be used for hedging real estate stocks. Olson et al (2019) studied the energy market and concluded that the cross-hedging strategy is not effective for managing price risk. In contrast, Chen and Tongurai (2021) used a crosshedging strategy and found that zinc and nickel contracts can be effectively used for managing the lead and tin cash exposure respectively.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Meanwhile, the ensuing disruptions to global demand and supply chains have engendered irregular movements in energy prices (see also, Iyke and Ho 2020 ; Iyke 2020a ). Although the motivation to hedge oil market risks is justified by studies suggesting the search for alternative hedging options for oil market risks (see Selmi et al 2018 ; Olson et al 2019 ; Sharma and Rodriguez 2019 ; Okorie and Lin 2020 ), the pandemic period offers yet greater motivation in this regard. This is because the crisis affecting the market becomes heightened with other markets (e.g., equities and currencies) that could be available to investors for diversification, which have also been impacted adversely by the pandemic(see Gil-Alana and Claudio-Quiroga 2020 ; Salisu et al 2020a , b ; Sharma 2020 ; Iyke 2020b ; Narayan 2020b , c ; Narayan et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%